Integrated hydroprocessing and microbial biotransformation of coconut oil to α,ω-diacids - Bashu Dev Pardhe; Il-Ho Choi; Chang Hoon Lee; Woo-Young Jeon; Min-Jeong Jang; Hye-Jeong Lee; Sung-Hwa Seo; Young Su Kim; HyunA Park; Hwabong Jeong; Jongbeom Park; Kyung Taek Heo; et al. (Bioresource Technology, 2025)

Multistrain Probiotics Alleviate Diarrhea by Modulating Microbiome-Derived Metabolites and Serotonin Pathway - Jin-Ju Jeong; Yoo-Jeong Jin; Raja Ganesan; Hee Jin Park; Byeong Hyun Min; Min Kyo Jeong; Sang Jun Yoon; Mi Ran Choi; Satya Priya Sharma; You Jin Jang; Uigi Min; Jong-Hyun Lim; et al. (Probiotics and Antimicrobial Proteins, 2025)
Diarrhea, a common gastrointestinal symptom in health problems, is highly associated with gut dysbiosis. The purpose of this study is to demonstrate the effect of multistrain probiotics (Sensi-Biome) on diarrhea from the perspective of the microbiome-neuron axis. Sensi-Biome ( Lactiplantibacillus plantarum , Bifidobacterium animalis subsp. lactis , Lactobacillus acidophilus , Streptococcus thermophilus , Bifidobacterium bifidum , and Lactococcus lactis ) was administered in a 4% acetic acid–induced diarrhea rat model at concentrations of 1 × 10 8 (G1), 1 × 10 9 (G2), and 1 × 10 10 CFU/0.5 mL (G3). Diarrhea-related parameters, inflammation-related cytokines, and stool microbiota analysis by 16S rRNA were evaluated. A targeted and untargeted metabolomics approach was used to analyze the cecum samples using liquid chromatography and orbitrap mass spectrometry. The stool moisture content ( p < 0.001), intestinal movement rate ( p < 0.05), and pH ( p < 0.05) were significantly recovered in G3. Serotonin levels were decreased in the multistrain probiotics groups. The inflammatory cytokines, serotonin, and tryptophan hydroxylase expression were improved in the Sensi-Biome groups. At the phylum level, Sensi-Biome showed the highest relative abundance of Firmicutes . Short-chain fatty acids including butyrate, iso-butyrate, propionate, and iso-valeric acid were significantly modified in the Sensi-Biome groups. Equol and oleamide were significantly improved in the multistrain probiotics groups. In conclusion, Sensi-Biome effectively controls diarrhea by modulating metabolites and the serotonin pathway.

Impact of thawing methods and packaging sizes on the physicochemical and microbial quality of frozen kimchi - Hee Eun Kim; Yun-Jeong Choi; Dong Hyun Park; Min Jung Lee; Minji Kim; Sung Jin Park; Ji Young Choi; Mi Ran Kang; Sung Hee Park; Mi-Ai Lee (International Journal of Refrigeration, 2025)

Deciphering the links: Fragmented polystyrene as a driver of skin inflammation - Gyeong Bae Song; Jisoo Nam; Sangmin Ji; Gijeong Woo; Soojeong Park; Bokyung Kim; Jeein Hong; Myung Gil Choi; Seokheon Kim; Chaerin Lee; Wonchul Lim; Sangwoon Yoon; et al. (Journal of Hazardous Materials, 2024)

Increased shinorine production through the introduction of mycosporine-like amino acids biosynthetic genes from Pyropia yezoensis and Nostoc punctiforme into Nannochloropsis gaditana - Sokyong Jung; Jong‑Min Lim; Sung-Ran Min; Gwang Hoon Kim; Won-Joong Jeong (Plant Biotechnology Reports, 2024)

Insights into tissue accumulation, depletion, and health risk assessment of clopidol in poultry - Wenting Wang; Min-Chul Shin; Sang-Hee Jeong; Jeong-Ran Min; Jong-Su Seo; Jong-Hwan Kim (Food Additives & Contaminants: Part A, 2024)

Antiperiodontitis impact of extract from edible herb Aster glehni and its bioactive compound, 3,5-dicaffeolyquinic acid - Gweon Ah Kang; Sung Ran Yoon; Yong Jin Jeong; Min-sook Kang; Haeng-ran Kim; Han-Seung Shin; Seok-Seong Kang (Food Bioscience, 2024)

Isolation and characterization of high-CO2 sensitive Nannochloropsis salina mutant - Jong-Min Lim; Sokyong Jung; Sung Ran Min; Won-Joong Jeong (Plant Biotechnology Reports, 2023)

RETRACTED ARTICLE: T1 transgenic tobacco plants carrying multicopy T-DNAs at the same locus exhibit various expression levels of transgenes - Sung Ran Min; Seyed Javad Davarpanah; Youn-il Park; Jae Heung Jeon; Jae Sun Moon; Jang Ryol Liu; Won Joong Jeong (Plant Biotechnology Reports, 2023)

Radiological Investigation of Gas Embolism in the East Asian Finless Porpoise (Neophocaena asiaeorientalis sunameri) - Adams Hei Long Yuen; Sang Wha Kim; Sung Bin Lee; Seyoung Lee; Young Ran Lee; Sun Min Kim; Cherry Tsz Ching Poon; Jun Kwon; Won Joon Jung; Sib Sankar Giri; Sang Guen Kim; Jeong Woo Kang; et al. (Frontiers in Marine Science, 2022)
Cetaceans have long been considered biologically adapted to suffer no adverse effects from diving-related tissue gas tension. However, increasing reports of gas embolism in cetaceans inhabiting European, Mediterranean and American waters have challenged the conventional understanding of marine mammal diving physiology. In human hyperbaric medicine, virtopsy techniques such as post-mortem computed tomography (PMCT) facilitate the visualization of gas embolism and could be performed adjunct to conventional autopsy. This research presents the first case of gas embolism identified in an East Asian finless porpoise inhabiting Asian waters. Massive gas embolic lesions were found in the liver, which had been compressing both the lungs and abdominal organs, and signs of pneumonia and parasitic infection were observed in both lungs. It is hypothesized that this porpoise might have been unable to expel in vivo gas bubbles from its circulation due to pulmonary dysfunction. Consequently, gas bubbles agglomerated in the liver, resulting in the development of gas embolic lesions. The findings of the present study provide insights into the occurrence of gas embolism in the East Asian finless porpoise, highlighting the potential of PMCT as a promising tool for the diagnosis of gas embolism in stranded cetaceans.

Production of porphyra-334 in transgenic lines of Nannochloropsis salina by the expression of mycosporine-like amino acid biosynthetic genes of P. yezoensis - Jae-Sun In; Jong-Min Lim; Sokyong Jung; Dong-Woog Choi; Sung-Ran Min; Won-Joong Jeong (Journal of Applied Phycology, 2021)

Characterization of the copper-sensing transcriptional regulator CopR from the hyperthermophilic archeaon Thermococcus onnurineus NA1 - Seo-Yeon Kim; Hong Joo Jeong; Minwook Kim; Ae Ran Choi; Min-Sik Kim; Sung Gyun Kang; Sung-Jae Lee (BioMetals, 2019)

Loss of copy number and expression of transgene during meiosis in Pyropia tenera - Jong-Min Lim; Yoon Ju Shin; Sokyong Jung; Seung A. Choi; Dong-Woog Choi; Sung Ran Min; Won-Joong Jeong (Plant Biotechnology Reports, 2019)

Enhanced tolerance to heat stress in transgenic tomato seeds and seedlings overexpressing a trehalose-6-phosphate synthase/phosphatase fusion gene - Jae Il Lyu; Ji Hyun Park; Ju-Kon Kim; Chang-Hyu Bae; Won-Joong Jeong; Sung Ran Min; Jang R. Liu (Plant Biotechnology Reports, 2018)

Characterization of high temperature-tolerant strains of Pyropia yezoensis - Yoon Ju Shin; Sung Ran Min; Da Yeon Kang; Jong-Min Lim; Eun-Jeong Park; Mi Sook Hwang; Dong-Woog Choi; Joon-Woo Ahn; Youn-Il Park; Won-Joong Jeong (Plant Biotechnology Reports, 2018)

l-carnosine induces apoptosis/cell cycle arrest via suppression of NF-κB/STAT1 pathway in HCT116 colorectal cancer cells - Jooyeon Lee; Jeong-Ran Park; Hanbyeol Lee; Soojin Jang; Se-Min Ryu; Hyejin Kim; Donguk Kim; Aera Jang; Se-Ran Yang (In Vitro Cellular & Developmental Biology - Animal, 2018)

Reduced gene expression at the branch point of chlorophyll and heme biosynthesis in Arctic Chlorella ArM0029B - Vikramathithan Jayaraman; Kwon Hwangbo; Jong-Min Lim; Sung Ran Min; Joon-Woo Ahn; Dong-Woog Choi; Won-Joong Jeong (Plant Biotechnology Reports, 2017)

Characterization of PyGUS gene silencing in the red macroalga, Pyropia yezoensis - Yoon Ju Shin; Jong-Min Lim; Ji Hyun Park; Dong-Woog Choi; Mi Sook Hwang; Eun-Jeong Park; Sung Ran Min; Suk Weon Kim; Won-Joong Jeong (Plant Biotechnology Reports, 2016)

Ethnobotany of the wild edible plants gathered in Ulleung Island, South Korea - Homervergel G. Ong; Jae-Min Chung; Hye-Ran Jeong; Young-Dong Kim; Kyung Choi; Chang-Ho Shin; You-Mi Lee (Genetic Resources and Crop Evolution, 2016)

The fate of extrachromosomal DNAs in the progeny of plastid-transformed tobacco plants - Sung Ran Min; Seo Hee Jung; Jang R. Liu; Won-Joong Jeong (Plant Biotechnology Reports, 2015)

An episomal vector system for plastid transformation in higher plants - Sung Ran Min; Seyed Javad Davarpanah; Seo Hee Jung; Youn-il Park; Jang R. Liu; Won-Joong Jeong (Plant Biotechnology Reports, 2015)

Isolation of human dermis derived mesenchymal stem cells using explants culture method: expansion and phenotypical characterization - Jeong-Ran Park; Eunjeong Kim; Jungwon Yang; Hanbyeol Lee; Seok-Ho Hong; Heung-Myong Woo; Sung-Min Park; Sunghun Na; Se-Ran Yang (Cell and Tissue Banking, 2015)

Nicotine inhibits the proliferation by upregulation of nitric oxide and increased HDAC1 in mouse neural stem cells - Hanbyeol Lee; Jeong-Ran Park; Jungwon Yang; Eunjeong Kim; Seok-Ho Hong; Heung-Myong Woo; Se-Min Ryu; Sung-Joon Cho; Sung-Min Park; Se-Ran Yang (In Vitro Cellular & Developmental Biology - Animal, 2014)

ENA-A actimineral resource A extends lifespan associated with antioxidant mechanism in SMP30 knockout mice - Jung-Youn Han; Meeyul Hwang; Sung-Yong Hwa; Jin-Kyu Park; Mi-Ran Ki; Il-Hwa Hong; Ah-Young Kim; Eun-Mi Lee; Eun-Joo Lee; Chang-Woo Min; Kyung-Ku Kang; Myeong-Mi Lee; et al. (Molecular and Cellular Biochemistry, 2014)

Synechocystis PCC6803 and PCC6906 dnaK2 expression confers salt and oxidative stress tolerance in Arabidopsis via reduction of hydrogen peroxide accumulation - Jonghyun Kim; Myung Suk Ahn; Young Min Park; Suk Weon Kim; Sung Ran Min; Weon Joong Jeong; Jang R. Liu (Molecular Biology Reports, 2014)

Overexpression of a trehalose-6-phosphate synthase/phosphatase fusion gene enhances tolerance and photosynthesis during drought and salt stress without growth aberrations in tomato - Jae Il Lyu; Sung Ran Min; Jeong Hee Lee; Yoong Ho Lim; Ju-Kon Kim; Chang-Hyu Bae; Jang R. Liu (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

Overexpression of AtATM3 in Brassica juncea confers enhanced heavy metal tolerance and accumulation - Mohammed Shafi Ullah Bhuiyan; Sung Ran Min; Won Joong Jeong; Sayeda Sultana; Kwan Sam Choi; Youngsook Lee; Jang R. Liu (Plant Cell, Tissue and Organ Culture (PCTOC), 2011)

The Protective Effect of ENA Actimineral Resource A on CCl4-Induced Liver Injury in Rats - Il-Hwa Hong; Hoon Ji; Sung-Yong Hwa; Won-Il Jeong; Da-Hee Jeong; Sun-Hee Do; Ji-Min Kim; Mi-Ran Ki; Jin-Kyu Park; Moon-Jung Goo; Ok-Kyung Hwang; Kyung-Sook Hong; et al. (Marine Biotechnology, 2011)

First complete genomic characterization of two tick-borne encephalitis virus isolates obtained from wild rodents in South Korea - Seok-Min Yun; Su Yeon Kim; Young Ran Ju; Myung Guk Han; Young Eui Jeong; Jungsang Ryou (Virus Genes, 2011)

Overexpression of a yeast cadmium factor 1 (YCF1) enhances heavy metal tolerance and accumulation in Brassica juncea - Mohammed Shafi Ullah Bhuiyan; Sung Ran Min; Won Joong Jeong; Sayeda Sultana; Kwan Sam Choi; Won Yong Song; Youngsook Lee; Yong Pyo Lim; Jang R. Liu (Plant Cell, Tissue and Organ Culture (PCTOC), 2011)

High-level expression of a human β-site APP cleaving enzyme in transgenic tobacco chloroplasts and its immunogenicity in mice - Jung Won Youm; Jae Heung Jeon; Hee Kim; Sung Ran Min; Mi Sun Kim; Hyouk Joung; Won Joong Jeong; Hyun Soon Kim (Transgenic Research, 2010)

Rapid and simple method for DNA extraction from plant and algal species suitable for PCR amplification using a chelating resin Chelex 100 - Kwon HwangBo; Su Hyun Son; Jong Suk Lee; Sung Ran Min; Suk Min Ko; Jang R. Liu; Dongsu Choi; Won Joong Jeong (Plant Biotechnology Reports, 2010)

Stable Plastid Transformation in Nicotiana benthamiana - Seyed Javad Davarpanah; Seo Hee Jung; Yaw Joo Kim; Youn-Il Park; Sung Ran Min; Jang Ryol Liu; Won Joong Jeong (Journal of Plant Biology, 2009)

Engineering the Japanese encephalitis virus RNA genome for the expression of foreign genes of various sizes: Implications for packaging capacity and RNA replication efficiency - Sang-Im Yun; Yu-Jeong Choi; Xiao-Fang Yu; Jae-Young Song; Young-Hak Shin; Young-Ran Ju; Seok-Yong Kim; Young-Min Lee (Journal of NeuroVirology, 2007)

The complete chloroplast genome sequences of Solanum tuberosum and comparative analysis with Solanaceae species identified the presence of a 241-bp deletion in cultivated potato chloroplast DNA sequence - Hwa-Jee Chung; Jong Duk Jung; Hyun-Woo Park; Joo-Hwan Kim; Hyun Wook Cha; Sung Ran Min; Won-Joong Jeong; Jang Ryol Liu (Plant Cell Reports, 2006)

An α3β4 subunit combination acts as a major functional nicotinic acetylcholine receptor in male rat pelvic ganglion neurons - Kyu-Sang Park; Seung-Kyu Cha; Min-Jeong Kim; Dae-Ran Kim; Seong-Woo Jeong; Joong-Woo Lee; In Deok Kong (Pflügers Archiv - European Journal of Physiology, 2006)

CHRK1, a chitinase-related receptor-like kinase, plays a role in plant development and cytokinin homeostasis in tobacco - Jeong Hee Lee; Kentaro Takei; Hitoshi Sakakibara; Hye Sun Cho; Do Myung Kim; Youn Sung Kim; Sung Ran Min; Woo Taek Kim; Dae Young Sohn; Yong Pyo Lim; Hyun-Sook Pai (Plant Molecular Biology, 2003)

Growth retardation of plants transformed by overexpression of NtFtsZ1-2 in Tobacco - Won Joong Jeong; Suk Won Jeong; Sung Ran Min; Ook Joon Yoo; Jang Ryol Liu (Journal of Plant Biology, 2002)